The association of physical activity and sedentary behavior with depression in US adults: NHANES 2007–2018 - Meng, Yanli; Ma, Ning; Shi, Yixin; Zhang, Ning; Wu, Jing; Cui, Xia; Niu, Wenquan (Frontiers in Public Health, 2024)
Objectives: Depression is largely preventable; strategies that can effectively suppress its development are imperative. We aimed to examine whether physical activity and sedentary behavior were associated with depression, and explore the possible mediatory role of complete blood count on this association.In this cross-sectional study, data were integrated from the National Health and Nutrition Examination Study (2007-2018). Depression was defined by the Patient Health Questionnaire-9. Risk for depression expressed as odds ratio (OR) and 95% confidence interval (CI) was quantified by survey-weighted Logistic regression analyses.Results: Total 31 204 respondents were analyzed. Significance was identified for all, except walking or bicycling per week, types of physical activity and sedentary behavior. Per 1 standard deviation (SD) increment in metabolic equivalent of task (MET) of weekly vigorous recreational physical activity was associated with 31.3% decreased depression risk (adjusted OR: 0.687, 95% CI: 0.5663-0.840). Per 1 SD increment in sitting time can increase depression risk by 22.4% (adjusted OR: 1.224, 95% CI: 1.131-1.325). In subsidiary analyses, the association with depression was reinforced in respondents aged ≤65 years and with overweight or obesity. Mediation analyses revealed significance for red blood cell (RBC) on total MET (19.4%) and MWPA (22.0%), for red cell distribution wide (RCDW) on vigorous work-related physical activity (17.7%), moderate work-related physical activity (13.1%), total MET (11.2%), and sitting time (16.4%) (P<0.01).Our findings indicate that more physical activity and less sitting time were associated with a lower likelihood of having depression among US adults, and this association was probably mediated by RBC and RCDW.